Cyber Security Featuresfor National E-Learning Policy - Buja, Alya Geogiana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes cybersecurity features in the National e-Learning policy. Cybersecurity in the learning environment is becoming an issue that has been considered by the community. DePAN 1.0 and DePAN 2.0 policies have not been carefully planned in any related security concerns. Amongst security domains in e-learning are authentication and accountability, access control, and non-repudiation issues. However, as the functionality of e-learning is expanding, information must be actively protected in this bigger context to avoid the loss of its confidentiality, integrity, and availability. Therefore, the existing policy and guidelines on e-learning have been studied thoroughly. A very feasible study has been conducted on the existing literature and related works to e-learning and e-learning. The security threats are also reviewed in this paper. Based on the established e-Learning policy, therefore, the proposed security features are namely (CSF1) authentication and accountability, (CSF2) access control, (CSF3) protection of communication, and (CSF4) non-repudiation issues. The findings from this study can be added to the implementation of e-learning in the future.